2012
DOI: 10.3892/etm.2012.511
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Wnt2B expression affects tumor proliferation and survival in malignant pleural mesothelioma patients

Abstract: Malignant pleural mesothelioma (MPM) is an aggressive thoracic tumor with a poor prognosis. We performed a comprehensive clinical study on the intratumoral expression of Wnt1, Wnt2B and Wnt5A in MPM. One hundred and seven MPM patients were investigated. Immunohistochemistry was performed to evaluate the intratumoral expression of Wnt1, Wnt2B, Wnt5A, survivin and c-Myc, and the Ki-67 proliferation index. The apoptotic index was evaluated by the TUNEL method. Among the 107 MPMs, 23 MPMs (21.5%) were Wnt1-high tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
1
18
0
1
Order By: Relevance
“…In the multivariate Cox regression analysis, it was found that the factors affecting survival were SKIP expression intensity, Ki-67 proliferation index and non-epithelioid histological type. In previous studies, it was reported that the Ki-67 proliferation index was higher in MPM cases and that survival periods were shorter [9,14]. Similarly, the Ki-67 proliferation index was higher in non-epithelioid cases in our study.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In the multivariate Cox regression analysis, it was found that the factors affecting survival were SKIP expression intensity, Ki-67 proliferation index and non-epithelioid histological type. In previous studies, it was reported that the Ki-67 proliferation index was higher in MPM cases and that survival periods were shorter [9,14]. Similarly, the Ki-67 proliferation index was higher in non-epithelioid cases in our study.…”
Section: Discussionsupporting
confidence: 64%
“…Biomarkers such as survivin, fibulin-3 and mesothelin have also been suggested as prognostic factors to predict poor outcome in MPM, but they are not sufficient for use as prognostic biomarkers [8,9,10]. It is known that the Ki-67 proliferation index increases in MPM patients and that it is related to poor prognosis [9,14]. In HCC, alterations in SKIP expression and the Ki-67 proliferation index were found to be correlated, and it was reported that the increase of both of them is a short survey indicator in HCC patients [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kobayashi et al demonstrate that Wnt2b plays a positive role in the proliferation of mesothelioma[28]. Similarly, Wang et al report that silencing Wnt2b significantly diminishes proliferation in several ovarian cancer cell lines[29].…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck squamous cell carcinoma, WNT2B played a role in tumourigenesis and chemotherapy resistance in vivo and in vitro [23]. Intratumoural WNT2B was reported to be correlated with the expression of Survivin and c-Myc, tumour proliferation and prognosis in malignant pleural mesothelioma [24]. Jiang et al also found that the high-expression level of WNT2B was associated with the progression and worse outcome of pancreatic cancer [25].…”
Section: Discussionmentioning
confidence: 99%